30 years of wilms tumor experience at one center in türkiye's central anatolia region - Akyol, Sefika; Odabas, Gul Pelin; Ozcan, Alper; Yilmaz, Ebru; Karaman, Zehra Filiz; Ozturk, Figen; Akgun, Huelya; Dogan, Ahmet Burak; Eroglu, Celalettin; Unal, Ekrem; Karakukcu, Musa; Ünal, Ekrem (İstanbul Üniv., 2023)
Objective: The current study aims to evaluate the clinical presentation, treatment, and follow-up of children with Wilms Tumor (WT) who had been admitted to Erciyes University, Faculty of Medicine Department of Pediatric Hematology and Oncology hospital, a tertiary center in the central Anatolia region of Turkiye. The study assesses the survival data and features that have had an impact on survival. Materials and Methods: The current study has been planned as a retrospective observational evaluation of patients admitted to the Pediatric Hematology and Oncology Center between 1991-2021. Results: The study retrospectively evaluated a total of 48 patients in terms of demographic characteristics, presentation findings, tumor stages, histopathologies, and survival rates. Patients with an unfavorable histology had a 66.7% chance of both event-free survival (EFS) and overall survival (OS), which is lower than the respective 85.2% and 92.1% odds of EFS and OS for the favorable histology group. However, this is not statistically significant (p = 0.20 for EFS and p = 0.05 for OS). Regarding the impact of stage on survival rates, the EFS and OS for patients with the low-stage disease were 88% and 95.7%, respectively. These rates were significantly superior to those at an advanced stage of the disease, whose EFS and OS were 63.1% and 60.9%, respectively (p = 0.042 for EFS, p = 0.005 for OS). Conclusion: Wilms tumor at an advanced stage and with an unfavorable histology are the major factors resulting in poor survival rates.
Keywords: Wilms Tumor; Event-Free Survival; Overall Survival; Unfavorable Histology